2014
DOI: 10.4103/2141-9248.144921
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of dental prosthetic status and prosthetic needs among eunuchs (trans genders) residing in Bhopal City, Madhya Pradesh, India: A cross-sectional study

Abstract: Background:Eunuchs are considered as the most vulnerable, frustrated, and insecure community. The accessibility to medical and dental facilities for the eunuchs is nearly nonexistent. Due to these reasons, they might be at a high risk of developing severe dental problems like tooth loss.Aim:The present cross-sectional study aimed to evaluate the dental prosthetic status and prosthetic needs among eunuchs residing in Bhopal city, Madhya Pradesh, India.Subjects and Methods:On the basis of convenient nonprobabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…In the present study, almost a quarter of the study population needed prosthetic treatment in one form or the other, which was higher than the findings of another study in India (51.5%). [11] The reason for this great difference in prosthetic needs may be due to the reason that our majority of the study population were in the elderly age group in their study. Of the 291 conditions studied between 1990 and 2010 in the Global Burden of Disease Study, it was found that oral diseases were highly prevalent affecting 3.9 billion people worldwide.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the present study, almost a quarter of the study population needed prosthetic treatment in one form or the other, which was higher than the findings of another study in India (51.5%). [11] The reason for this great difference in prosthetic needs may be due to the reason that our majority of the study population were in the elderly age group in their study. Of the 291 conditions studied between 1990 and 2010 in the Global Burden of Disease Study, it was found that oral diseases were highly prevalent affecting 3.9 billion people worldwide.…”
Section: Discussionmentioning
confidence: 96%
“…[13] According to Hongal et al , a\the attitudes of the community towards special groups like the eunuchs, have been reflected even in the health care settings. [11] Most of the health-care facilities are concentrated only with respect to HIV or other sexually transmitted diseases and oral health takes a back seat.…”
Section: Discussionmentioning
confidence: 99%
“…Deogade et al . [ 21 ] and Slade et al . [ 18 ] observed that the need for full prostheses was more than the need for multiunit prostheses or the need for a combination of one and multiunit prosthesis in females.…”
Section: Discussionmentioning
confidence: 99%
“…noted that the need for single-unit prosthesis was highest among females, and males were required more multiunit prosthesis. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…Gender is defined as a spectrum that encompasses and distinguishes the two concepts masculinity and femineity, based on the interplay of biological sex, sex‐based social structure, and gender identity 1 . However, when there is no consistency between sex at birth and gender identity or expression, the person is denominated as transgender 2 . High rates of unemployment, workplace discrimination, physical abuse, depression, drug use, exposure to health risk factors, and social stigma have all plagued transgender people 1,2 .…”
Section: Introductionmentioning
confidence: 99%